GLOBAL CAPITALISM, ECONOMIC CRISES, AND TH E IR IMPACT ON NIGERIA’S EDUCATION SECTOR - Ibrahim, Sani (Sokoto Educational Review, 2011)
Economic recessions occur even’ ten years or so; they are cyclical in nature. Whenever a recession occurs, measures are taken to ensure non-occurrence. Yet the occurrence occurs. The paper examines whether it is the measures taken to ensure non-occurrence that is faulty or it is the basic structure of the capitalist economic system that is faulty. The paper touches on the meaning and philosophy of capitalism and the nature of the economic recession. The paper also examines the implications of the crises in Nigeria’s education sector, which include the sector’s inability to employ more urgently needed teaching personnel. The paper concludes that the capitalist economic system, as it presently is, lias some structural defects that need to be corrected, for example, the philosophy that government should not regulate the economy. Seven recommendations are made. One of them is that stricter banking regulation and supervision all over the world are required.